Metal urethral stent placement for the management of urethral stricture following phalloplasty: a case report - He, Hu; Zhong, Chuanhua; Chen, Qiang; Lei, Yongsheng; Chen, Longchao; Li, Lulu; Zhang, Xin; Pan, Jinhong; Zhang, Heng (Frontiers in Urology, 2025)
ObjectiveTo report the preliminary experience of a case in which a thermo-expandable nickel-titanium shape memory alloy metal stent was utilized for the management of urethral stricture following phalloplasty.MethodsA 51-year-old male patient underwent lower abdominal island flap phalloplasty due to penile trauma. Postoperative recurrent dysuria occurred, and urethrography revealed stricture at the urethral anastomosis site near the penile root. A thermo-expandable nickel-titanium shape memory alloy metal stent was implanted.ResultsThe patient underwent a successful surgical procedure. One day after the surgery, the urethral catheter was removed, and the patient resumed normal urination. After achieving satisfactory outcomes, the patient recovered and was discharged. During regular follow-up visits after discharge, the patient maintained unobstructed urination without weak urine stream or other discomforts.ConclusionsThe placement of a thermo-expandable nickel-titanium shape memory alloy metal stent offers a novel treatment option for patients with urethral stricture following phalloplasty